Pelatihan Perancangan Sop Pengelolaan Dana Dan Penyajian Laporan Keuangan Berbasis Sak Etap Pada UPTD Balai Pendidikan Dan Pelatihan Provinsi Sumatera Barat - Riani Sukma Wijaya; Ratnawati Raflis; Murniati Murniati; Eka Mariyanti; Enny Arita (Jurnal Pengabdian Masyarakat Dharma Andalas, 2023)
This community service activity is aimed at cooperative managers who still lack an understanding of creating cooperative financial reports in accordance with the PSAK ETAP (Indonesian Financial Accounting Standards for Small and Medium Enterprises). The activity is conducted at the Cooperative Technical Implementation Unit (UPTD) and involves the participation of 40 cooperative managers from various regions in West Sumatra.In this regard, their knowledge and ability to prepare cooperative financial reports are limited. There is a lack of an effective accounting information system as a basis for accurate financial reporting, and insufficient control over cooperative operational activities. As a result, the presentation of financial reports serves as a performance report for managers or a report of cooperative management accountability.The method designed for this activity starts with providing practical experience in creating financial reports and establishing Cooperative Financial Recording Standard Operating Procedures (SOP) using flowcharts. With the implementation of this training, cooperative managers will be capable of creating Cooperative Financial Reports and designing cooperative SOPs that align with the needs of the cooperatives they manage.